EVALUATION OF THE EFFECTIVENESS OF DIFFERENT CULTURE MEDIA ON THE DOMESTICATION OF FRESHWATER LOBSTER (Cherax quadricarinatus): EVALUASI EFEKTIVITAS MEDIA PEMELIHARAAN YANGBERBEDA PADA DOMESTIKASI LOBSTER AIR TAWAR(Cherax quadricarinatus) - Nurhatijah; Kurnia; Indah Permatasari; Humeira; Rossy Azhar; Masyitah; Dedek Zulvira (PT. ROCE WISDOM ACEH, 2025)
This study aimed to investigate the role of different culture media in the domestication process on the survival rate of freshwater lobster (Cherax quadricarinatus). The study employed a field experimental method with four treatment groups, namely freshwater media, flowing water media, plankton-enriched water media, and Lactobacillus-enriched water media. The results showed that freshwater lobster's survival rate (SR) ranged from 26% to 97%. The freshwater media treatment had the highest SR value (97%), while the Lactobacillus-enriched water media treatment had the lowest SR value (26%). Analysis of water quality parameters indicated that temperature, pH, and other water quality parameters met the standards required for freshwater lobster cultivation. The results of this study suggest that the application of different culture media can maintain the survival rate of freshwater lobster.